Statistical atlases and computational models of the heart : ACDC and MMWHS challenges : 8th International Workshop, STACOM 2017, Held in Conjunction with MICCAI 2017, Quebec City, Canada, September 10-14, 2017, Revised selected papers /: ACDC and MMWHS challenges : 8th International Workshop, STACOM 2017, Held in Conjunction with MICCAI 2017, Quebec City, Canada, September 10-14, 2017, Revised selected papers. (2018) - Unknown
No abstract available